Experiences and Challenges of a New Palliative Care Service in the United Arab Emirates - Neil A. Nijhawan; Humaid O. Al-Shamsi (Palliative Medicine and Hospice Care, 2022)
Introduction Palliative care as a medical subspecialty in the United Arab Emirates (UAE) is very much in its formative stage of development. There are a small number of healthcare facilities that provide a specialist palliative care service, the most recent of which is the Palliative and Supportive Care Service at Burjeel Medical City (BMC), a private hospital in Abu Dhabi. Aim This retrospective review of all the referrals to our palliative and supportive care service within the first 9-months of operation is a direct reflection of the challenges we currently face in the day-to-day delivery of palliative care in the UAE. Result Of a total of 360 referrals received during the study period, under 50% were for local, Emirati patients with international expatriates making up the rest. Most of the referrals received were for symptom control (including pain) and end-of-life care (EoLC), with 85% of the patients having a diagnosis of cancer. One third of the referrals received were for EoLC, with 90% of the pa-tients who received EoLC on a hospital ward having a valid do not attempt resuscitation (DNAR) status in place. For the patients who received EoLC, all but one patient received EoLC in the hospital setting. Conclusion Our experiences are consistent with the challenges that other colleagues in the Middle East and North Africa (MENA) region face in providing palliative care. The majority of referrals to the palliative and supportive care service were for patients with a di-agnosis of cancer with only 15% reflecting a non-cancer diagnosis. Of the 150 decedents cared for during this study period, more than 75% had a valid DNAR status in effect suggesting a growing awareness and acceptance of a less medicalized EoLC period.